Grasshoppers and their kin - Hutchins, Ross E (New York Dodd & Mead, 1972)
Text and photographs introduce the physical characteristics and habits of grasshoppers and related insects such as katydids, walking sticks, and crickets.
Bibliography: p. 141.
1
Keywords: Orthoptera -- Juvenile literature